IMPACT OF LIBRARIANS’ MANAGERIAL SKILLS ON THE DEVELOPMENT OF RESOURCES AND QUALITY SERVICES IN THE UNIVERSITY LIBRARIES OF PAKISTAN - Zahid Sultan; Dr. Shamshad Ahmed (IJoLIS, 2025)
Abstract Purpose This study aims to investigate the influence of librarians’ managerial skills on the quality service and library resources in university libraries of Pakistan Methodology A survey was conducted among librarians in Pakistani universities to assess their managerial skills, including library management skill, decision making and budget management. The study also evaluated the quality and accessibility of library resources. Limitations The study was limited to Pakistani universities and may not be generalizable. to other countries or context. Key findings The findings reveal that librarians with strong managerial skills significantly influence the quality and availability of library resources. By integrating advance technology and strategic planning, librarian support education and research effectively. Practical implication(S) Practical implications The study highlights the importance of enhancing managerial skills to improve library services benefiting educators stakeholders end the government by bridging knowledge gap and fostering conducive learning of environment. Contribution to knowledge The study contributes to understanding of the role of librarians managerial skills in enhancing library services and resources which is crucial for creating a more knowledgeable and empowered society.